Effect of Rapid Thermal Annealing Temperature on the Electrophysical Properties of the Ohmic Contact of Ti/Al/Ni Metallization to the GaN/AlGaN Heterostructure - A. D. Yunik; J. A. Solovjov; D. V. Zhyhulin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
Effect of rapid thermal annealing temperature on the electrophysical properties of the ohmic contact of Ti/Al/Ni metallization with layer thicknesses of 20/120/40 nm to the GaN/AlGaN heterostructure with a two-dimensional electron gas on a sapphire substrate has been discovered by transmission line measurement and secondary ion mass spectroscopy methods. Rapid thermal annealing of the samples was carried out in a nitrogen atmosphere at the temperature ranging from 850 to 900 °C for 60 s. It has been discovered that a high-resistance heterostructure layer with a thickness of about 25 nm is located on the initial samples between metallization and the two-dimensional electron gas, which prevents the formation of ohmic contact. After rapid thermal annealing at the temperature of less than 862,5 °C, the metallization components interact with each other and with the heterostructure, which leads to the decrease in the thickness of the high-resistance heterostructure layer to 15–20 nm and to the nonlinearity of the I – V characteristic. At rapid thermal annealing temperatures in the range from 862,5 to 875 °C, the thickness of the high-resistance heterostructure layer decreases to several nanometers due to the interaction of Ti/Al/Ni metallization components with the heterostructure, which promotes the tunneling effect of charge carriers and formation of a high-quality ohmic contact with a resistivity of about 1⸱10–4 Ohm∙cm2 . With an increase of the rapid thermal annealing temperature over 875 °C, the interaction of the metallization and heterostructure components occurs throughout the entire depth, the two-dimensional electron gas degrades, and the I – V characteristic of the contact becomes nonlinear. The results obtained can be used in the technology for creating GaN-based products with a two-dimensional electron gas.